Biomineralization regulation by nano‐sized features in silk fibroin proteins: Synthesis of water‐dispersible nano‐hydroxyapatite. Issue 8 (28th March 2014) - Huang, Xiaowei; Liu, Xi; Liu, Shanshan; Zhang, Aili; Lu, Qiang; Kaplan, David L.; Zhu, Hesun
Abstract In the present study, silk fibroin (SF) was used as a template to prepare nano‐hydroxyapatite (nano‐HA) via a biomineralization process. We observed that the content of SF affected both the morphology and water dispersibility of nano‐HA particles. Scanning electron microscope (SEM), transmission electron microscopy (TEM), X‐ray diffraction (XRD), zetasizer, and Fourier transform infrared spectroscopy (FTIR) were used to examine nano‐HA particle features including the surface morphology, aggregation performance, and crystallization. Rod‐like nano‐HA particles with desired water dispersibility were achieved when the ratio of SF/HA (calculated) was above 7:3. SEM, TEM, and zeta potential results revealed that nano‐HA particles were enclosed by the SF which formed a negative charge layer preventing the aggregation of HA nanoparticles in aqueous solution. Moreover, the nano‐HA particles were able to re‐disperse in water without precipitation for two weeks at room temperature, 60°C, and 90°C. Our work suggested a facile and effective approach of designing water‐dispersible nano‐HA particles which may have wide potential application in tissue engineering especially bone regeneration. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 1720–1729, 2014.